Urban and Rural Variants of Pre-industrial Demographic Regimes in Nineteenth-Century Brazil - Marcílio, Maria (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
Preliminary research in nineteenth-century Brazilian demographic data already indicates patterns different from the Old Regime model formulated for Europe. For Brazil there emerge four demographic regimes, involving degrees of isolation of population, access to natural resources, kinds of work, and relationship to the world economy: 1) subsistence economies; 2) plantation economies; 3) the slave population; and 4) urban areas, mostly ports. The slave population maintained its numbers by steady importation from Africa; the cities, by purchase of slaves and immigration from Europe.